Phasing analysis on DRO with impulsive maneuver - Fu, Honglan; Wang, Ming; Zhang, Hao (Frontiers in Astronomy and Space Sciences, 2023)
The cis-lunar periodic orbit exhibits some unique dynamic characteristics. Among them is the distant retrograde orbit, which has long-term stability and is one of the ideal candidate deployment orbits for cis-lunar space stations and deep-space exploration transfer stations. Orbiting, rendezvous, and docking are among the flight operations involved in space station on-orbit construction, material supply, spacecraft monitoring, and other tasks. Suitable initial conditions can be created for these operations by shortening the relative distance between spacecraft through phasing. In this study, the characteristics of a two-impulse phasing orbit on a distant retrograde orbit (DRO) are summarized, and its phasing ability is globally analyzed. Based on these analyses, a phasing optimization problem was presented and solved. Using DRO’s dynamic characteristics, a DRO multi-impulse phasing rolling solution method is presented. For accuracy purposes, the orbit determination error is also considered in this method. The simulation analysis was performed using the circular restricted three-body problem (CR3BP) dynamic model and the ephemeris model. Compared with the results of two-impulse phasing, this method reduces the offset of the end position of the DRO phasing orbit from hundreds to tens of kilometers. This result satisfies the relative distance requirements for subsequent spacecraft operations. The total pulse requirement of this phasing method for the two models was within a reasonable and feasible range.